Diagnostic Utility of Mean Peak Systolic Velocity of Superior Thyroid Artery in Differentiating Graves’ Disease from Thyroiditis - Sarangi, Pradosh K.; Parida, Sasmita; Mangaraj, Swayamsidha; Mohanty, Binoy K.; Mohanty, Jayashree; Swain, Basanta M. (Indian Journal of Radiology and Imaging, 2021)
Background Differentiating Graves’ disease from thyroiditis can be at times clinically challenging. The gold standard test (thyroid nuclear imaging scan) is expensive, not routinely available, and has radiation exposure. Color Doppler ultrasonography of thyroid represents a suitable alternate which can be used for differentiating these conditions by studying thyroid blood flow parameters.Aim We aimed to investigate the use of thyroid blood flow parameters’ assessment of the superior thyroid artery (STA) and common carotid artery (CCA) with color Doppler ultrasonography for differentiating Graves’ disease from thyroiditis.Materials and Methods This is a cross-sectional study on 111 patients with newly diagnosed thyrotoxicosis (82 with Graves’ disease and 29 with thyroiditis) and 45 years of age and sex-matched healthy controls. All patients underwent detailed clinical and necessary investigations. Color Doppler ultrasonography of the thyroid gland and spectral flow analysis of both superior thyroid arteries was done using standard protocol. Sensitivity and specificity for mean peak systolic velocity of STA (STA-PSV) cut-offs were calculated using receiver operating characteristic curves.Results Patients with Graves’ disease have significantly higher free tri-iodothyronine (FT3) levels, free thyroxine (FT4) levels, antithyroid stimulating hormone receptor antibody (TRAb) levels, and thyroid volume as compared with those with thyroiditis. The mean STA-PSV of patients with Graves’ disease was significantly higher than thyroiditis and control group. Mean STA-PSV greater than 54.3 cm/s had 82.9% sensitivity and 86.2% specificity in diagnosing Graves’ disease. Mean PSV-STA/PSV-CCA ratio of 0.40 was 80.5% sensitive and 86.2% specific for Graves’ disease.Conclusion Mean STA-PSV has high sensitivity and specificity in differentiating Graves’ disease from thyroiditis and can be used routinely in clinical practice as a cheap and invaluable diagnostic tool.
Keywords: color Doppler; Graves’ diseases; peak systolic velocity; superior thyroid artery; thyroiditis; thyrotoxicosis